(untitled) - FOS (Illinois, 1991)
This book builds step by step. Chapter 1 covers how power trains work. Chapter 2-10 go into detail about the different kinds of power trains and their working parts. Each chapter clearly dicusses how to adjust and maintain its power train systems as well as how to diagnose and test problem areas
Keywords: agricutural mechanics